Plastic surgery training in the UK: Results from a national survey of trainee experiences. (September 2020) - Fell, Matthew; Staruch, Robert; Baker, Benjamin G; Nicholas, Rebecca; Howes, Rachel; ,; Amin, Kavit; Coelho, James; Collins, Michelle; Concannon, Elizabeth; Din, Asmat; Hendrickson, Susan; et al.
Abstract: Background: Plastic surgery training in the UK continues to evolve towards an outcome-based rather than time-served curriculum. UK plastic surgery trainees are appointed nationally, and are assessed according to national standards, but training is delivered regionally. This study sought opinion from current UK plastic surgery trainees in order to highlight strengths and shortcomings of the higher surgical training programme. Method: A cross-sectional study was designed and administered by the UK Plastic Surgery Trainees Association (PLASTA). A questionnaire was distributed to all UK plastic surgery trainees holding a National Training Number, using the REDCap web-based application. Results: Of the 320 UK plastic surgery trainees, 131 (41%) participated in this survey, with responses from all 12 UK training regions. The most common subspecialty career aspirations for trainees were hand surgery, cleft lip and palate, lower limb and oncoplastic breast reconstruction. The survey highlighted regional variation in teaching programmes, the ability to achieve indicative operative logbook numbers, and training in aesthetic surgery. Of the trainees, 82% expressed a desire to undertake a fellowship within their training, but most did not know whether their deanery would support this. Fifteen per cent of the respondents were currently training flexibly and the majority of these had experienced negative behaviours towards their less than full time working status. Of the respondents, 44% reported stress, 25% reported a lack of autonomy and 17% reported feeling burnt out at work at least once a week. A total of 85% perceived that they did not have access to a mentoring service. Conclusions: Plastic surgery remains a popular and highly competitive surgical speciality in the UK, and many trainees reported high levels of satisfaction during their training. Aspects of training that could be improved have been highlighted and recommendations made accordingly.